Pengaruh Aplikasi CapCut: Menyelami Kreativitas dengan Ragam Template Video yang Memukau pada Generasi Z - Sekaringtyas, Fia Wahyu; Djuniadi, Djuniadi; Hastawan, Ahmad Fashiha (FORMAT, 2024)
Technology, especially video editing apps like CapCut, has become an integral part of Generation Z's life in the digital age. CapCut provides intuitive features and a variety of templates to create engaging video content without the need for complex editing skills. In interviews with Generation Z students, CapCut's key features such as crop, speed, audio, text, transitions, filters, overlays, and templates were found to be attractive and supportive in the creative process. Nonetheless, there is a need to continue developing the app by adding more template options and providing greater flexibility for users in customizing content. Thus, CapCut can continue to be a relevant and effective tool for Generation Z in expressing themselves in the ever-evolving digital era.